OYO: Growth, Descend, Resilience, Resurgence. Issue 2 (December 2022) - Kumar, Raj; Singh, Jagandeep
The year 2021 had drawn to a close. OYO, the India-based hotel start-up that had witnessed a pandemic-induced descent in business, appeared to have ticked the right boxes and was on a resurgence path. Founded in 2013, OYO grew rapidly in its initial years and had operations in 800 cities in 80 countries in 2019, just prior to the onset of COVID-19. It was the 'fastest growing' hotel chain in the world. Burgeoning losses at the time compelled OYO to make a strategic shift from aggressive growth to an accretive growth strategy. In the mid of its course correction endeavour, OYO's business plunged in wake of COVID-19. OYO exhibited resilience and strived for resurgence even though it remained in the red. What were the resource-based and position-based sources of competitive advantage that propelled OYO's meteoric rise initially and enabled it to remain resolute in the COVID-19 crisis? Can OYO be termed as successful in light of the Balanced Scorecard framework? What strategic options are available to OYO to maintain its growth trajectory in the post-pandemic phase?